Nihi Sumba Resort’s corporate social responsibility as philanthropy activities - Ni Putu Virgin Kartika Sari; I Ketut Astawa (International Journal of Green Tourism Research and Applications, 2020)
Purpose: This research aimed to analyze corporate social responsibility (CSR) conducted by Nihi Sumba Resort in relation to the philanthropy activities run by Sumba Foundation as the NonGovernment Organization pointed by the resort to hold their CSR activities.Research methods: Data analysis was done through descriptivequalitative methods by examining the three clusters of policy, which are International, national and local policy, to elaborate whether the conduction has been following the clusters rule or not.Results and discussion: The results showed that CSR activities run by Nihi Sumba Resort were not only incidentally CSR but a sustainable one, especially in relation to the ecosystem of the island. The driving factors of CSR were as a form of moral obligation, to improve the company image, and to gain profit.Conclusion: The conduction also has been well handled according to the cluster of the policies, with the extra benefit of the ecological impacts of the CSR programs are the minimization of energy consumption generated through the use of vernacular concepts in all existing properties.